Nature, Enlightenment, and university reforms in the Iberian Peninsula: a comparative analysis of the Universities of Salamanca and Coimbra (1766-1820) - Teixeira Alves, Carlos Fernando (Historia de las Universidades, 2024)
The university reforms that took place in Europe throughout the 18th century were an important moment of change in the history of these institutions. In the Iberian Peninsula, this wave of reforms left its mark in Coimbra and Salamanca (later reaching the other Spanish universities). Portugal and Spain were no strangers to the motivations and even to the general lines of this wave of reforms. Inseparable from the ideas of the Enlightenment, and with a clear will to combat the backwardness and decadence of these institutions, rather ambitious projects emerged, albeit in different degrees. Coimbra faced a rather disruptive initial situation while in Salamanca later plans (1807, for example) proved to be quite ambitious as well. All having a mandatory nature, it would not be correct to say that these Universities did not participate in these processes of reform. Individually or on behalf of collective bodies, several initiatives and proposals emerged during this period in both Universities. In addition, the participation of professors in the statutes and plans that were launched since 1771 is recurrent. Beyond this aspect, it will not be forced to state that the curricular aspect was the most significant mark of these reforms. Thus, we chose to study in a comparative way subjects that sought to explain the concept of nature and its products. With the clear objective of preparing a body of technicians capable of providing a rational and effective exploitation of the various natural products, the faculties of mathematics and philosophy emerged. In the case of medicine, natural products were essential to produce medicines and in this sense the reform of this knowledge brought, among other changes, matters linked to pharmaceutical studies. In the area of law, a relevant introduction was natural law. The perception of natural law was not similar in both countries, and an evident consequence was the greater instability of this chair in Salamanca. Inseparable from the curricular aspects was the adoption of foreign compendia and the encouragement given to the teachers to write their own textbooks. The adoption of textbooks was quite similar, and clearly shows us the lines that reformers sought to follow to modernize these university institutions.